Crisis and General International Law: Lessons from the Russia-Ukraine Conflict - Alexander, Atul (UI Scholars Hub, 2023)
The ongoing Russian aggression in eastern Ukraine has instilled fear in humanity, with concerns of a possible third world war. Furthermore, international law has been criticized for its lackadaisical role in halting the Russian aggression. The United Nations Security Council (UNSC) has not been able to pass a resounding resolution condemning the attacks. Although the United Nations General Assembly (UNGA) overwhelmingly adopted a resolution demanding that Russia immediately cease military operations in Ukraine, the resolution is not binding, despite being persuasive. This brief article highlights the structural crisis in general international law to effectively combat the tragedy unfolding in Ukraine. Some of the structural shortcomings studied include consent, veto, lack of accountability and flimsy sanctions regime. This paper is divided into two main themes. Firstly, it maps the structural crisis in general international law in the context of the ongoing Russia-Ukraine conflict. Secondly, it provides a possible solution to address these issues. A structural crisis refers to a simultaneous crisis in many fields of international law, or what might be called a generalized crisis. It is concluded that although general international law provides several avenues to overcome these structural crises, it has failed to deliver due to a lack of will from the States.